Workforce Strategic Importance:Boosting Organizational Performance - Jessica Verga Ananta; Sidiq Permono Nugroho (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study explores how the strategic significance of the workforce and HR flexibility toward strategic human capital capabilities affects organizational performance in higher education institutions, with the research centered on the Faculty of Economics and Business at Universitas Muhammadiyah Surakarta. The research highlights how human capital adaptability and strategic alignment serve as critical determinants of organizational success.Methodology: A quantitative approach was applied by distributing structured questionnaires to 72 permanent lecturers, assessed utilising a five-point Likert scale. Data were analysed utilising Partial Least Squares-Structural Equation Modelling (PLS-SEM) via SmartPLS 4.0 to evaluate construct validity, reliability, and the structural relationships among the variables. The conceptual model comprises four fundamental constructs: Workforce Strategic Importance, HR Flexibility, Strategic Human Capabilities, and Organizational Performance.Results: The results show that Workforce Strategic Importance and HR Flexibility produce positive yet statistically insignificant direct effects on Organizational Performance. However, both factors considerably strengthen Strategic Human Capabilities, which subsequently exert a strong positive impact on Organisational Performance. The results demonstrate that Strategic Human Capabilities serve as a vital mediating mechanism that translates the impact of HR initiatives into enhanced performance outcomes.